Hydrous RuO2‐Decorated MXene Coordinating with Silver Nanowire Inks Enabling Fully Printed Micro‐Supercapacitors with Extraordinary Volumetric Performance. Issue 15 (25th February 2019) - Li, Hongpeng; Li, Xiran; Liang, Jiajie; Chen, Yongsheng
Abstract: The fabrication of fully printable, flexible micro‐supercapacitors (MSCs) with high energy and power density remains a significant technological hurdle. To overcome this grand challenge, the 2D material MXene has garnered significant attention for its application, among others, as a printable electrode material for high performing electrochemical energy storage devices. Herein, a facile and in situ process is proposed to homogeneously anchor hydrous ruthenium oxide (RuO2 ) nanoparticles on Ti3 C2 T x MXene nanosheets. The resulting RuO2 @MXene nanosheets can associate with silver nanowires (AgNWs) to serve as a printable electrode with micrometer‐scale resolution for high performing, fully printed MSCs. In this printed nanocomposite electrode, the RuO2 nanoparticles contribute high pseudocapacitance while preventing the MXene nanosheets from restacking, ensuring an effective ion highway for electrolyte ions. The AgNWs coordinate with the RuO2 @MXene to guarantee the rheological property of the electrode ink, and provide a highly conductive network architecture for rapid charge transport. As a result, MSCs printed from the nanocomposite inks demonstrate volumetric capacitances of 864.2 F cm −3 at 1 mV s −1, long‐term cycling performance (90% retention after 10 000 cycles), good rate capability (304.0 F cm −3 at 2000 mV s −1 ), outstanding flexibility, remarkable energy (13.5 mWh cm −3 ) and power density (48.5 W cm −3 ). Abstract : A fully printed strategy is reported to assemble flexible micro‐supercapacitors by printing thixotropic nanocomposite inks for electrodes comprising RuO2 · x H2 O@Ti3 C2 T x (MXene) nanosheets and silver nanowires. The resultant screen‐printed micro‐supercapacitors based on this RuO2 · x H2 O@MXene–AgNW nanocomposite ink exhibit a landmark volumetric capacitance of 864.2 F cm −3 at a scan rate of 1 mV s −1 .